Development of the technology of «Mozzarella» goat cheese with specified functional properties - Z. N. Khatko; M. A. Gasheva; S. K. Kudainetova (Новые технологии, 2021)
The article shows the prospects for the production of Mozzarella cheese of goat milk and dry sourdough. Cheese contains vital nutritional components, they are biologically complete and play an important role in the diet. Searching for new resources is an urgent problem. The solution may be to expand the range of cheeses not only of cow milk, but also of other farm animals, for example, goats. Their milk is absorbed faster and is used in medical and preventive nutrition. On the consumer market goat milk products are mainly represented by farms, and their range is small. The authors carried out the research on the selection of starter cultures containing probiotic cultures from bifidobacteria, acidophilus bacillus and thermophilic streptococcus, to optimize the technological process for the production of Mozzarella cheese based on goat milk. These cultures represent a beneficial microflora that inhabits the human body, helping to absorb nutrients and digest food. An important quality of probiotics that ensures their physiological effect is their high growth rate and compatibility with other microorganisms present in the gastrointestinal tract. It has been found that all the studied samples of goat milk in terms of composition have indicators that meet the requirements of GOST for goat milk. Comparative analysis of cow and goat milk has shown predominant indicators of the quality of goat milk in comparison with cow milk. The processes of coagulation and fermentation of goat milk under the influence of various starter cultures have been studied. The use of ABT-5-Probio-TecTM probiotic starter culture, which accelerates the technological process and imparts functional properties to the product, has been substantiated. The possibility of using goat milk in the production of cheeses with cheddaring and thermomechanical processing has been proven. Microscopic examination of a sample of Mozzarella cheese on ABT-5 sourdough has shown that bifidobacteria survive after heat treatment at high temperatures.